2022
DOI: 10.3390/medicina59010090
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Effect of the Coronavirus Disease 2019 Pandemic on Emergency Department Visits in Korea

Abstract: Background and Objectives: The ongoing coronavirus disease 2019 (COVID-19) pandemic represents a global public health crisis that has had a serious impact on emergency department (ED) utilization trends. The aim of this study was to investigate the collateral effects of the COVID-19 pandemic on ED utilization trends by patients with mild and severe conditions as well as on 7-day fatality rates. Materials and Methods: We analyzed entries in the Korean National Health Insurance claims database between 1 January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that the COVID-19 pandemic had a significant adverse collateral impact on the operation of emergency departments. For example, Cho et al, in the case of Korean emergency department patients, identified collateral impact on the emergency department patients in the form of increased in-house mortality during the pandemic [ 35 ]. In their conclusions, they recommend that further investigation should be performed to analyze the causes of the increased fatality.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the COVID-19 pandemic had a significant adverse collateral impact on the operation of emergency departments. For example, Cho et al, in the case of Korean emergency department patients, identified collateral impact on the emergency department patients in the form of increased in-house mortality during the pandemic [ 35 ]. In their conclusions, they recommend that further investigation should be performed to analyze the causes of the increased fatality.…”
Section: Resultsmentioning
confidence: 99%